Mathematical software -- ICMS 2018 : 6th International Conference, South Bend, IN, USA, July 24-27, 2018, Proceedings /: 6th International Conference, South Bend, IN, USA, July 24-27, 2018, Proceedings. (2018) - Unknown
No abstract available